EXPLORING HALAL CERTIFICATION MENTORING UNDER THE SELF-DECLARE SCHEME: A CASE STUDY OF MSMES IN CIANJUR AND JATINANGOR - Wibowo, Bambang Aji; Yuliafitri, Indri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Indonesia holds significant potential in developing its halal industry; however, many micro, small, and medium enterprises (MSMEs) have yet to obtain halal certification due to financial constraints and limited access to information. To address this issue, BPJPH launched the Self-Declare scheme and the Free Halal Certification program (SEHATI). Although the process is simplified, many business owners still struggle to understand the certification procedures through the SIHALAL platform. This study aims to examine the mentoring process for halal certification under the Self-Declare scheme for MSMEs in Cianjur and Jatinangor. Using a qualitative case study method, data were collected through observation and direct mentoring of seven MSMEs without halal certification. The mentoring process was carried out in three main stages: socialization of the free halal certification program, issuance of Business Identification Numbers (NIB) and SIHALAL account registration, and the distribution of halal certificates for MSMEs that passed verification. The results show that the mentoring successfully helped all seven MSMEs obtain halal certification and improved their understanding of the importance of halal certification in maintaining consumer trust. However, several challenges remain, such as limited understanding of the SIHALAL system, administrative difficulties with required documents, and the restricted SEHATI quota, which hampers other MSMEs from obtaining certification. In conclusion, the Self-Declare and SEHATI schemes have proven effective in assisting MSMEs to acquire halal certification. Nevertheless, broader outreach and more intensive mentoring are necessary to ensure more business owners can optimally benefit from these programs.